The influence of Employer Psychological Contracts breach and its impact to employees' innovative behaviors (A qualitative study in research organization in Malaysia) - Bashah, Mohd Helmi Ali; Idris, Khairuddin; Harun, Zubaidah; Othman, Jamilah; Mohamad Yasin, Murni; Omar, Zoharah; Zainal, Hasnyanti (Imperial Publishing House, 2016)
The objectives of this study is to examine the influences the Employer Psychological Contract (EPC) breach and its effects on employees’ innovativeness. An interviews has been conducted in a focus group with 5 numbers of participants. The findings discussed the variety of ways employees’ perceive on contract breach in their research organization. From the literatures, the study also found that EPC and its impacts to the employees’ innovativeness are rarely discussed. The findings are based on the interview results and analysis employer career development, trust, rewarding and support could help to improve psychological contracts and its relationship towards employees’ innovativeness. The studies giving an overview on how EPC breached could affect the employees’ innovative behaviors based on a focus group interviews.